Hubungan Malaysia dengan Britain era Dr. Mahathir, 1981-1990 / Mohd Afendi Daud - Mohd Afendi , Daud (2016)
Many studies have been done by scholars either locally or abroad on Dr. Mahathir Mohamad. But not much research has focused on Malaysia’s external relations with Britain during the Mahathir era, 1981-1990. Thus, this study examines in depth aspects of the relations between Malaysia and Britain. Mahathir is internationally known as a leader who has criticized the West and has been labelled as anti-West. The Third World countries, however, view him differently and have labelled him as a Third World spokesman. For Malaysia, he is a leader who is quite different from previous leaders, especially in respect of his views of the West. This thesis is divided into eight chapters, the first chapter begins with an introduction and is followed by a background discussion of Malaysia’s relationship with Britain. Chapter three describes Dr. Mahathir’s rise to leadership. The study then examines important aspects beginning with the economic aspect of bilateral relations in chapter four. Chapter 5, 6 and 7 discuss the political, education and defence aspect of bilateral relations. Chapter 8 is a conclusion to this study. This thesis found that Dr. Mahathir implemented the Buy British Last (BBL) policy in protest against Britain’s arrogant attitude and indifference toward several issues raised by Malaysia. One of the major issues that alienated Malaysia’s relations with Britain is the implementation of the New Economic Policy which required cooperation from Britain but which was not taken seriously by Britain. The study also looked at the impact of the BBL on the relationship between Malaysia and Britain. The implementation of the BBL led to a change in Britain’s attitude towards Malaysia and was a turning point in relations between Malaysia and Britain. This study clearly shows that there was a significant change in Malaysia’s relations with Britain during the Mahathir era from 1981 to 1990.